Unlocking Employee Potential; Crafting an Effective Human Resource Strategy to Increase Teachers’ Motivation - Kamal Hasan (Journal of Research in Educational Management, 2023)
This qualitative research study delves into the realm of human resource management strategies aimed at elevating the motivation levels of quality employees within educational institutions. The research centers on the practices employed by the principal, as they endeavor to enhance the overall quality of human resources within the institution. Quality, in this context, encompasses a dynamic state that pertains to products, individuals, processes, tasks, and the environment, meeting or surpassing the expectations of customers and consumers. The findings underline the pivotal role of human resource management in fostering quality employees, with motivation emerging as a fundamental catalyst. Motivation is revealed as the driving force behind the cultivation of competent human resources, serving as the impetus for specific behaviors aimed at achieving predefined objectives. Several characteristics of motivation are identified, including its roots in fulfilling needs, its focus on goals, and its ability to sustain desired behaviors. In essence, this research underscores the significance of motivation in nurturing and advancing human resources within organizations. It emphasizes the imperative of maintaining a constant state of motivation among employees, ensuring their continuous commitment to meet the demands of their roles and responsibilities within the organization.